Hibiscus sabdariffa-sourced zinc oxide nanoparticles: optimization, characterization, and cytotoxicity on brine shrimp - Yumni Baharom, Ain; Norman, Ashreen; Che Abdullah, Che Azurahanim (John Wiley and Son, 2025)
In the last decade, nanotechnology has received a lot of attention. Zinc oxide nanoparticles (ZnONPs) and their properties, such as antibacterial, antifungal, anticancer, and photocatalytic abilities, have long been studied. Furthermore, green synthesis from plant-based sources has numerous advantages over traditional physical and chemical methods. The green synthesis of ZnONPs is performed in this study using roselle extract (Hibiscus sabdariffa). During the fabrication of metal nanoparticles, the plant extract acts as a reducing and capping agent. Taguchi design is used to optimize and evaluate synthesis parameters like pH, temperature, and reaction time. Dynamic light scattering (DLS) is used in conjunction with this statistical method to determine the optimal parameters for reducing particle size to nanometers. DLS measurements reveal that the average size of the ZnONPs range from 341.7 to 546.5 nm. XRD analysis reveals that the crystallite sizes of the ZnONPs range from 12.7 to 73.8 nm. X-ray diffraction (XRD) analysis reveals that the ZnONPs has a wurtzite crystal structure. Ultraviolet visible spectrophotometer (UV–vis) reveals bandgaps are measured for the best samples. They are calculated to be 3.74, 3.64, and 3.35 eV, respectively. Fourier transform infrared spectroscopy (FTIR) analysis reveals that a variety of bioactive compounds are responsible for ZnONP stabilization. Thermogravimetric analysis (TGA) exhibits that synthesized ZnONPs lost little weight, demonstrating their high thermal stability. Furthermore, brine shrimp hatching assays are used to assess biogenic ZnONP toxicity.